Palladium-catalyzed desulfinative cross-couplings - de Gombert, A; Willis, MC (Cell Press, 2020)
The Suzuki–Miyaura reaction has undeniably revolutionized the art of synthesis, particularly in the pharmaceutical industry. However, the coupling of 2-pyridine boronic acids has long remained a challenge. In this context, our laboratory has recently reported the use of pyridyl and other heteroaryl sulfinate salts as efficient alternatives to boron reagents. This new reaction successfully yields industrially relevant building blocks, the synthesis of which would be challenging using classic boron-based nucleophiles.